Pengembangan Media Pembelajaran Aritmatika Sekolah Dasar Menggunakan Powerpoint Interaktif - Sugianti Sugianti; Arin Yuli Astuti; Rifqi Rahmatika Az-Zahra (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The influence of early mathematics learning and learning motivation on student learning outcomes is very significant [1]. Students' numeracy literacy skills need to be supported by the ability to learn mathematics as early as possible. Advanced mathematics learning needs to be supported by good arithmetic skills. Every learning process is expected to produce good learning outcomes. Conventional mathematics learning is difficult for low-level students to understand. Guidebooks that are in accordance with the learning curriculum tend to present mathematical concepts that are textual. In order for mathematics learning to be more interesting for students, it is necessary to develop learning media that are easily accessible to students and educators. One application that can be used is interactive Powerpoint [2]. In this community service, a learning media about arithmetic was developed that underlies every logic of calculation in advanced mathematics. Assistance was given to students in grade III of elementary school, with the pretest method, presentation of material using interactive Powerpoint media, and posttest. The validation test of the learning media was carried out by educators by providing an average test result of 84.36%. The results of this community service state that arithmetic learning media using interactive Powerpoint can be used in grade III of elementary school.